Global geographic and gender disparities in stem cell-related surgical research: bibliometric review of the top 200 most-cited articles - Russell Seth Martins; Aqsa Muhammad Nasir; Zobiyah Sajid Charolia; Alina Pervez; Omar Mahmud; Hamzah Jehanzeb4 (Journal of the Pakistan Medical Association, 2023)
Objective: The study aimed to identify geographic and gender disparities in the quality, academic impact, and media attention of the top-cited articles related to stem cell-related surgical research. Methods: The following data was extracted for the top 200 most-cited articles (2011-2021): article- (including citation metrics and country of publication), journal- (including impact factor), and author-level (including corresponding author gender) variables. Article Altmetric Attention Score (AAS), a measure of mass mainstream and social media attention, was also recorded. Results: Most articles originated from high-income countries (HICs: 175 [87.5%]), with only 7 (3.5%) from lower-middle-income countries. Articles from non-HIC were published in journals with significantly lower impact factors (6.66 [3.75-9.46] vs. 23.2 [7.3-32.5]; p < 0.001) and AAS (7 [3-14.5] vs. 30 [11-83]; p < 0.001). Only 44 (22%) of articles were authored by a female corresponding author, Continued..